2008
DOI: 10.1164/rccm.200710-1522oc
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the NHE1 Gene Prevents Hypoxia-induced Pulmonary Hypertension and Vascular Remodeling

Abstract: Rationale: Our previous studies found that Na 1 /H 1 exchanger (NHE) activity played an essential role in pulmonary artery smooth muscle cell (PASMC) proliferation and in the development of hypoxiainduced pulmonary hypertension and vascular remodeling. Other investigators recently observed increased expression of the NHE isoform 1 (NHE1) gene in rodents with pulmonary hypertension induced by hypoxia. However, a causal role for the NHE1 gene in pulmonary hypertension has not been determined. Objectives: To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 48 publications
(56 reference statements)
4
84
2
Order By: Relevance
“…Studies also showed that the inhibition of NHE1 by inhibitors attenuated the hypertrophy of cardiomyocytes (23)(24)(25)(26)(27). Because we also found a significant decrease in the medial wall thickness of pulmonary arteries in NHE1-deficient mice with decreased hypoxic pulmonary hypertension and vascular remodeling (11), we hypothesized that the effects of NHE1 on hypoxia-induced PASMC hypertrophy were also mediated via E2F1. In addition, the migration of PASMCs is reportedly involved in the pathogenesis of pulmonary hypertension (28), and hypoxia and smooth muscle growth-stimulating factors were shown to affect the migration of PASMCs (29)(30)(31).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Studies also showed that the inhibition of NHE1 by inhibitors attenuated the hypertrophy of cardiomyocytes (23)(24)(25)(26)(27). Because we also found a significant decrease in the medial wall thickness of pulmonary arteries in NHE1-deficient mice with decreased hypoxic pulmonary hypertension and vascular remodeling (11), we hypothesized that the effects of NHE1 on hypoxia-induced PASMC hypertrophy were also mediated via E2F1. In addition, the migration of PASMCs is reportedly involved in the pathogenesis of pulmonary hypertension (28), and hypoxia and smooth muscle growth-stimulating factors were shown to affect the migration of PASMCs (29)(30)(31).…”
mentioning
confidence: 77%
“…We previously determined that p27, a cyclin-dependent kinase inhibitor and an upstream factor of E2F1, plays a critical role in inhibiting the proliferation of PASMCs and the pulmonary hypertension induced by hypoxia (17)(18)(19). We also observed a significantly decreased expression of cyclin D1, a downstream factor of p27 and upstream factor of E2F1, in PASMCs isolated from NHE1-deficient mice with decreased hypoxic pulmonary hypertension and vascular remodeling (11). We therefore assumed that the inhibition of NHE1 caused a reduction of PASMC proliferation via the E2F1 regulatory pathway.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…A potential role for calcineurin in artery remodeling is interesting in the context of acid-base transport because we and others have reported that NHE1 is important for artery structure development and remodeling (10,49,50). Further investigations are required to determine whether changes in NBCn1 activity induced by calcineurin inhibitors contribute to the observed effects on artery remodeling.…”
Section: Discussionmentioning
confidence: 98%
“…In Nhe1 −/− mice, there was a decrease in ROCK expression and activity, an increase in the expression of p27 (a cyclindependent kinase inhibitor and known downstream factor of ROCK), and a decrease in cyclin D1 expression. 100 Moreover, expression of E2F1, a transcription factor important in cell cycle progression that is known to be downstream of p27, was upregulated by hypoxia in human PASMCs, and this upregulation was inhibited in the setting of in vitro NHE1 silencing. 67 The role of E2F1 as a downstream effector of NHE1 was further confirmed by the fact that overexpression of E2F1 prevented the decrease in PASMC proliferation and migration observed when NHE1 was silenced.…”
Section: Rock P27 and Cyclin D1 Signalingmentioning
confidence: 99%